On education - Krishnamurti (Chenai, India : Krishnamurti foundation, 1998)
This book is the outcome of talks and discussion held by J Krishnamurti with the students and teachers of Rishi Valley School in Andhra Pradesh and Rajghat Besant School in Varanasi. Krishnamurti regards education as of prime significance in the communication of that which is central to the transformation of the human mind and the creation of a new culture. As the topics in these stimulating talks and discussions reveal, he questions the very roots of our culture so that a comprehensive view on education emerges. Krishnamurti's challenge is addressed not only to the structure of education but to the very nature and quality of man's mind and life. Unlike all other attempts to salvage or suggest alternatives to the educational system, his approach breaks through the frontiers of particular cultures and establishes an entirely new set of values. To Krishnamurti a new mind is possible only when the religious spirit and the scientific attitude form part of the same consciousness. While he gives emphasis to the cultivation of the intellect, he lays far greater stress on a heightened critical awareness of the inner and outer world.
Keywords: Education -- Philosophy